Estratégias midiáticas em sites de organizações privadas: a busca pela visibilidade da responsabilidade social organizacional - Sgorla, Fabiane (2009)
Over history, the technological development, observed mainly from the nineties onwards, has made possible for private organisations to expose a variety of organizational information through media spaces such as television, newspaper and radio visibility which became known as media visibility. In the present days, Internet and Web facilities, such as the possibility of building organizational Websites, have played an important role in widening the media visibility from these organizations by operationalizing several media strategies. For bearing humanistic, solidarian and environmental concerns usually valued by the audience the information regarding corporate social responsibility has become more and more visible in organizational Websites. Within this reasoning in mind, this research study aims to reflect on the media visibility of organizational social responsibility in private organizations Websites. The empirical corpus was formed by 44 private organizations with headquarters in Rio Grande do Sul State, manufacturing and commercializing shoes and associated to the Brazilian Association of Shoes Industry (Associação Brasileira de Indústrias de Calçados - Abicalçados). The specifics research objectives were: to discover if the selected organizations have Websites; to examine whether the information concerning social responsibility are shown in these Websites; to verify if the expressions social responsibility , environmental responsibility and/or social and environmental responsibility combined together are used in these Websites; to identify and analyze the main strategies for presenting the information concerning social responsibility in the Websites of the studied organizations. The empirical analysis had mainly a qualitative approach in which the descriptive and interpretative method was used. The collecting method comprehended the observation of the Websites from the selected organization. The analysis of the data happened simultaneously to its collection. The main results show that 86% of the organizations, in other words, thirty eight (38) of them have organizational Websites. Within these thirty eight (38) Websites, 42% display information regarding social responsibility and 32% make use of the expressions social responsibility and/or environmental responsibility . The presentation strategies of this information in the Websites were related to seven (7) categories: Company, Social Responsibility, Environmental Responsibility, News, Sponsorship, Support and Activities e Social Report.